Penile ring entrapment and strangulation: A case report at Kampala International University Teaching Hospital in Western Uganda. (March 2021) - Kyomukama, Lauben Amagara; Ssebuufu, Robinson; Wani, Shaban Abdullah; Waziri, Musa Abbas; Lule, Herman
Highlights: Penile ring entrapment is when a ring previously inserted onto penis is left for extended period of recommended time. Delayed removal of the ring lead to strangulation that presents challenges to general surgeons and institution to manage it. Pilot bearing ball ring was removed by cutting with electrically powered angled grinder Abstract: Introduction: Penile ring entrapment during self-sexual satisfaction is one of the rare cases in general and urologic surgery. When the penile shaft is entrapped in a metal ring, one risks possible complete loss of distal penis to strangulation and gangrene. We present management of a case of entrapped penile ring with penile strangulation in resource limited set up amidst absence of management guidelines. The case has been reported in line with SCARE criteria (1). Presentation of case: A 43-year-old male presented after 72 h of pilot ball bearing ring penile insertion for sustainability of an erection, with 24 -h history of painful penile swelling and acute urine retention. The patient had history of using recreational drugs and erectile dysfunction with evidence of high-grade penile injuries at presentation. The ring was cut using electrically powered angled grinder, with full penile recovery on conservative management in eight months of follow up. Discussion: Entrapped penile ring is clinically diagnosed but establishing incentive of insertion is difficult just like identifying a correct technique to remove it. Entrapped ring obstructs blood and lymphatic flow leading to oedema and ischaemia with associated penile tissue injuries. High grade penile injuries or penile amputation are sequels of delayed ring removal and good outcomes are tangible through timely multidisciplinary approach. Conclusion: Eroticism and erectile dysfunctions are known incentive to using penile rings to sustain erection. Delayed ring removal results in its entrapment and penile strangulation and related complications. Timely removal of ring requires multidisciplinary approach and local management protocols.